Measuring Digital Power: The Urgency of Education in Technology - Giacomini, Gabriele (Scenari, 2023)
Foucault and Deleuze’s interpretations of power still implicitly inspire the research of many social scientists today. One example is Zuboff’s “surveillance capitalism”. With digital media, indeed, the operations of profiling and persuading citizens require to be at least problematised. Through empirical analysis, this article aims to identify certain characteristics of digital platforms (such as “neointermediation”) and to explore how Italians would like to reform these powerful organisations. In conclusion, the importance of a more deeply rooted and widespread digital literacy emerges.